Method for preparing porous ceramics using ultraviolet light-induced phase separation
Patent Information
- Application Number
- CN202611321240.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
其原因在于:陶瓷颗粒对紫外光的散射与衰减效应导致固化交联不均匀,干扰相分离的热力学与动力学平衡;高固含浆料的高黏度特性严重限制物质迁移,阻碍富集相区的生长与连通;大量陶瓷颗粒的拥挤占位对相区演化产生几何约束与界面干扰
(1)本发明通过特定组分比例显著改善了陶瓷浆料中的相分离行为。首先,本发明利用聚乙二醇等兼具亲水/亲油链段的物质作为相分离组分,使其与光固化树脂具有良好的相容性,同时又可均匀分布于陶瓷颗粒之间。其次,加入分散剂抑制陶瓷颗粒团聚。且,聚乙二醇等相分离组分兼具相分离组分与陶瓷粉体表面改性的双重功能,有利于构建均匀的分散网络,所得陶瓷浆料均表现出明显的剪切变稀行为,且在剪切速率为100s-1下的粘度均在3mPa·s以下,为后续光固化过程中的相分离行为提供了均一的物质基础和界面环境,确保相分离组分在固化网络中的分布一致性,从而有利于后续形成分布均匀的孔结构。
Smart Images

Figure CN122916630A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous ceramics, and more particularly to a method for preparing porous ceramics using ultraviolet light-induced phase separation. Background Technology
[0002] Porous ceramics possess characteristics such as low density, large specific surface area, high temperature resistance, corrosion resistance, and good chemical stability, making them widely used in filtration and separation, catalyst supports, thermal insulation and sound absorption, biological scaffolds, and sensors. Their performance depends not only on the composition of the ceramic material but also on porosity, pore size, pore morphology, and spatial distribution. Therefore, achieving controllable fabrication of the internal pore structure of ceramic components is an important research direction in the field of porous ceramic manufacturing.
[0003] In existing technologies, ceramic pore formation typically employs methods such as pore-forming agents, templates, foaming, gel casting, and freezing. While these methods can create pores within the ceramic, the pore structure is easily affected by factors such as the size, morphology, and dispersion state of the pore-forming agent. In particular, when the pore size is reduced to the micrometer scale, problems such as local pore agglomeration and difficulty in adjusting pore connectivity can easily occur, making it difficult to achieve controllable construction of the internal pore structure of the ceramic.
[0004] Phase separation technology is mainly used for pore formation in low-solids systems such as aerogels. Its application in high-solids materials like ceramics is currently undocumented. This is because: the scattering and attenuation effects of ultraviolet light by ceramic particles lead to uneven curing and cross-linking, interfering with the thermodynamic and kinetic equilibrium of phase separation; the high viscosity of high-solids slurries severely restricts mass migration, hindering the growth and connectivity of enriched phase regions; and the crowding of numerous ceramic particles creates geometric constraints and interfacial interference on phase evolution. These factors are coupled, resulting in insufficient phase separation, poor phase connectivity, and poor pore structure uniformity in ceramic materials. This increases the difficulty of applying phase separation technology to ceramics and makes precise control of the pore structure difficult. Summary of the Invention
[0005] In view of this, the present invention proposes a method for preparing porous ceramics using ultraviolet light-induced phase separation. By using ultraviolet light-induced phase separation technology, a porous structure is generated in situ in the ceramic material, and the porous structure is precisely controlled, thereby obtaining a porous structure with uniform distribution and adjustable pore size.
[0006] The technical solution of this invention is implemented as follows: This invention provides a method for preparing porous ceramics using ultraviolet light-induced phase separation, comprising the following steps: Step S1: Under light-protected conditions, ceramic powder, photocurable monomer, photoinitiator, non-photopolymerizable phase separation component and dispersant are mixed evenly to obtain ceramic slurry; Step S2: The above ceramic slurry is cured by light to obtain a ceramic green body; Step S3: Remove organic matter from the ceramic green body and perform sintering treatment to obtain a sintered ceramic body with a porous structure.
[0007] During photopolymerization, the photopolymerizable monomers and photoinitiators in the ceramic slurry undergo photopolymerization to form a cross-linked polymer network, which solidifies and shapes the ceramic powder particles in situ. Simultaneously, the non-photopolymerizable phase components, which are compatible or partially compatible with the photopolymerizable components before the photopolymerization reaction, gradually separate from the polymer network as the photopolymerization reaction proceeds, i.e., they gradually precipitate out, forming an enriched phase. With increasing polymerization, the enriched phase grows and connects, eventually forming an independent microphase structure in the cured ceramic-polymer composite system. The enriched phase is then removed by cleaning and degreasing with solvents such as water, ethanol, and propanol, thereby forming micropores inside the ceramic corresponding to the morphology of the enriched phase.
[0008] Based on the above technical solutions, preferably, the photocurable monomer includes at least one of polyethylene glycol diacrylate (PEGDA), tripropylene glycol diacrylate (TPGDA), and polyurethane acrylate (PUA).
[0009] The non-photopolymerized phase-separated component includes at least one of polyethylene glycol (PEG), polypropylene glycol (PPG), and polyvinylpyrrolidone (PVP).
[0010] Polyethylene glycol (PEG), polypropylene glycol (PPG), or polyvinylpyrrolidone (PVP) serve a dual function in ceramic photocuring slurry systems: phase separation components and ceramic powder surface modification. On one hand, their hydrophilic segments can migrate to the surface of ceramic particles in non-aqueous media, inhibiting particle agglomeration through steric hindrance and achieving in-situ modification of the ceramic powder surface, thus improving its dispersion uniformity in the slurry. On the other hand, during photocuring, they act as non-photopolymerizing phase separation components, inducing the formation of enriched phases, subsequently generating uniformly distributed porous structures in situ. This synergistic effect not only ensures uniform pore distribution within the ceramic matrix but also avoids structural defects caused by uneven dispersion of traditional external pore-forming agents, resulting in porous ceramic materials with uniform pore structure and consistent performance.
[0011] The mass ratio of the photocurable monomer to the non-photopolymerized phase-separated component is (7:3) to (8:2).
[0012] Preferably, the pore size of the ceramic sintered body is 2.0~7.5μm.
[0013] In this invention, the mass ratio of photocurable monomer to phase-separating component is a key factor determining the pore structure of porous ceramics. When the mass ratio is greater than 8:2, the photocurable monomer dominates the system, and the content of the phase-separating component is too low, failing to form a sufficient enriched phase during photopolymerization, resulting in insufficient phase separation, low apparent porosity, and difficulty in interconnecting the pores. When the mass ratio is less than 7:3, the proportion of phase-separating component is too high. Although the apparent porosity is improved, the excessive phase-separating component reduces the proportion of the polymer skeleton and leads to an excessively rapid phase separation rate. This causes the enriched phase to overgrow and coarsen before the curing process is complete, disrupting the uniformity of the pore structure and the continuity of the ceramic skeleton, which is detrimental to maintaining the material's mechanical properties. Therefore, the mass ratio of photocurable monomer to phase-separating component needs to be controlled within a reasonable range to achieve regulation of the pore structure.
[0014] More preferably, in the ceramic slurry, The mass fraction of ceramic powder is 75-85%; The mass fraction of the dispersant is 1-3%; The total mass percentage of the photocurable monomer and the non-photopolymerized phase-separated component is 11% to 23.5%. The photoinitiator accounts for 0.5% to 1% of the total mass.
[0015] The composition of ceramic slurry is a key parameter determining its dispersion stability and photocuring behavior. The addition of dispersants aims to address the agglomeration of ceramic powders. When the dispersant's mass fraction is too low (<1%), it cannot form a sufficient steric hindrance layer on the surface of ceramic particles, resulting in predominantly van der Waals forces between particles, leading to agglomeration and sedimentation, and insufficient slurry dispersion stability. Conversely, when its mass fraction is too high (>3%), it increases slurry viscosity, hindering curing.
[0016] Regarding the sum of the mass of photocurable monomers and non-photopolymerizable phase components, if the proportion is too low (<11%), there will be insufficient polymerizable components in the system, resulting in low crosslinking density after curing and difficulty in meeting the subsequent sintering process requirements for green body strength; if the proportion is too high (>23.5%), the relative content of ceramic powder will decrease, the shrinkage rate will increase after sintering, leading to dimensional deviations and deformation cracking.
[0017] When the mass fraction of photoinitiator is too low (<0.5%), the polymerization reaction rate is slow, the curing time is prolonged and the curing depth is insufficient, and it does not match the phase separation rate, ultimately leading to uneven pore distribution. When the mass fraction is too high (>1%), the polymerization reaction is too violent, and the green body is prone to cracking due to volume shrinkage and internal stress concentration.
[0018] Based on the above technical solution, preferably, in step S2, the photocuring process parameters include: ultraviolet light wavelength 355nm~405nm, exposure dose 10~40mJ / cm2 .
[0019] The 355nm~405nm range falls within the near-ultraviolet region. This wavelength matches the absorption wavelength of photoinitiators, effectively exciting them to generate free radicals while avoiding excessive thermal damage to the resin system from excessively short wavelengths or reduced curing precision due to excessive penetration. Regarding exposure dosage, if it is below 10mJ / cm²... 2 Incomplete polymerization reaction leads to insufficient curing depth and low green strength; if it exceeds 40 mJ / cm 2 This would cause the polymerization reaction rate to be too fast, leading to volume shrinkage and increased internal stress, resulting in warping and cracking of the green body. Therefore, the wavelength should be controlled at 355–405 nm and the exposure dose at 10–40 mJ / cm². 2 This helps to obtain ceramic green bodies with complete structure and stable dimensions while ensuring curing efficiency and precision.
[0020] More preferably, the removal of organic matter from the ceramic green body in step S3 includes: The ceramic green body obtained in step S2 is cleaned and degreased to remove organic matter from the ceramic green body, resulting in a green body with a porous structure.
[0021] The degreasing process includes: placing the ceramic green body in an air atmosphere, heating it to 500~600℃, and holding it at that temperature for 2~6 hours.
[0022] Regarding the debinding temperature, 500~600℃ covers the thermal decomposition temperature range of organic components such as photocurable monomers and dispersants. At this temperature, the organic matter can be fully pyrolyzed into gaseous products and escape, while avoiding excessive sintering shrinkage of ceramic particles due to excessively high temperatures, thus achieving a balance between organic matter removal and skeletal stability. As for the holding time, if it is less than 2 hours, the organic matter decomposition is insufficient, and residual carbonaceous components will affect the density and properties of the ceramic during subsequent sintering; if it exceeds 6 hours, energy consumption increases, and abnormal grain growth or slight sintering of the green body may occur due to prolonged high temperatures, which is detrimental to the control of the subsequent densification process.
[0023] The present invention has the following advantages over the prior art: (1) This invention significantly improves the phase separation behavior in ceramic slurries through specific component ratios. First, this invention utilizes substances such as polyethylene glycol, which possess both hydrophilic and oleophilic segments, as phase separation components, ensuring good compatibility with photocurable resins while also allowing for uniform distribution among ceramic particles. Second, a dispersant is added to inhibit ceramic particle agglomeration. Furthermore, the phase separation components such as polyethylene glycol possess the dual functions of phase separation and ceramic powder surface modification, which is beneficial for constructing a uniform dispersion network. The resulting ceramic slurries all exhibit significant shear-thinning behavior, and at a shear rate of 100 s⁻¹, the phase separation behavior is significantly improved. -1The viscosity of the components is below 3 mPa·s, which provides a uniform material basis and interface environment for the phase separation behavior in the subsequent photocuring process, ensuring the consistent distribution of phase-separated components in the cured network, thus facilitating the formation of a uniformly distributed pore structure.
[0024] (2) This invention generates a three-dimensional interconnected porous structure in situ through photopolymerization-induced phase separation technology. During photopolymerization, phase separation components such as polyethylene glycol separate from the photopolymerization network. After subsequent degreasing and sintering, a porous structure with uniform distribution and interconnected channels is obtained. The apparent porosity of the sample can be controlled between 15% and 25%, indicating that the pore structure prepared by this invention has good repeatability and controllability.
[0025] (3) The present invention also achieves effective control of porous structure. By adjusting the molecular weight and addition amount of phase separation components, the thermodynamic driving force and kinetic path of phase separation can be changed, so that the pore size of porous ceramics can be precisely controlled within the range of 2.0~7.5μm. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a process flow diagram of the present invention.
[0028] Figure 2 The microstructures of different ceramic samples are shown, among which, Figure 2 a is the sample obtained from Comparative Example 1. Figure 2 b is the sample obtained from Comparative Example 3. Figure 2 c is the sample obtained in Example 1.
[0029] Figure 3 The apparent porosity and average pore size of the ceramic samples of Examples 1-5 and Comparative Examples 1-5 are shown.
[0030] Figure 4 The graph shows the viscosity variation of the ceramic slurry in Examples 1-3 and Comparative Example 2. Detailed Implementation
[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0032] In the following specific embodiments, PEGDA400, PEG200, TPO (diphenyl-(2,4,6-trimethylbenzoyl)phosphorus oxynitrate), tripropylene glycol diacrylate (TPGDA), polypropylene glycol (PPG), polyurethane acrylate (PUA1000), and polyvinylpyrrolidone (PVP) were all purchased from Sinopharm Chemical Reagent Co., Ltd., BYK-111 (dispersant) was purchased from BYK Chemical Co., Ltd., alumina powder was purchased from Beijing MCC New Material Technology Co., Ltd., and barium titanate ceramic powder was purchased from Shandong Guoci Functional Materials Co., Ltd.
[0033] Example 1 This embodiment provides a method for preparing porous ceramics using ultraviolet light-induced phase separation, the process flow of which is as follows: Figure 1 As shown, the specific method is as follows: Step 11: Weigh 8.8g of PEGDA400 and 2.2g of PEG200, heat them to 60℃ and add them to a light-proof container. Then add 1g of BYK-111 (dispersant) and 0.5g of TPO (diphenyl-(2,4,6-trimethylbenzoyl)phosphine). Mix the mixture for 15 minutes at 2000 r / min using a high-speed mixer to obtain a uniform photosensitive resin.
[0034] 75g of alumina ceramic powder was weighed and added to the above photosensitive resin in 5 batches. Premixing was performed after each addition of ceramic powder to reduce localized powder agglomeration. The premixed material was then loaded into a ball mill jar along with zirconia grinding balls at a mass ratio of 5:1. The mixture was ball-milled at 220 r / min for 4 hours to obtain a uniform and stable ceramic photosensitive slurry.
[0035] The uniformly mixed alumina slurry is placed in a vacuum degassing device to remove air bubbles introduced during mixing and ball milling.
[0036] Step 12: Use recognized 3D modeling software in the field to build a sample model, set the sample size to 10mm×10mm×5mm, and slice the model. Set the slice layer thickness to 50μm to obtain the slice file.
[0037] The alumina ceramic slurry to be cured was added to the slurry tank of a surface-exposure photopolymerization 3D printer. A uniform slurry layer with a thickness of 50 μm was formed by coating with a doctor blade. The target area was then subjected to ultraviolet surface exposure according to the sliced pattern. The ultraviolet light wavelength used for printing was 355 nm, and the irradiance at the exposed surface was 10 mW / cm². 2 The single-layer exposure time is 5 seconds. After one layer of exposure is completed, the relative position of the forming platform and the scraper is adjusted to the preset layer thickness of the next layer. The above material laying and exposure process is repeated, and the layers are accumulated until the entire sample is formed and the ceramic green body is obtained.
[0038] Step 13: Completely immerse the ceramic green body in ethanol and soak it at room temperature for 24 hours, while subjecting it to low-speed shaking. Place the ethanol-soaked ceramic green body in a 60℃ oven and dry it for 10 hours.
[0039] The dried ceramic green body underwent degreasing treatment, specifically as follows: It was placed in a vacuum tube furnace, and under continuous nitrogen protection, the temperature was increased from 50℃ to 600℃ at a rate of 0.5℃ / min. The temperature was then held at 150℃, 250℃, 350℃, 500℃, and 600℃ for 2 hours each, allowing residual PEG, cross-linked PEGDA400, TPO, and BYK-111 to gradually pyrolyze and dissipate, yielding an alumina ceramic preform. The alumina ceramic preform was then transferred to a muffle furnace, and the above heating and holding processes were repeated under an air atmosphere to remove residual carbon formed during the decomposition of organic matter in the degreasing process.
[0040] The degreased alumina ceramic preform was placed in a sintering furnace for sintering. First, the temperature was increased from 50℃ to 600℃ at a heating rate of 5℃ / min and held at 600℃ for 1 hour; then the temperature was increased from 600℃ to 900℃ at a heating rate of 3℃ / min and held at 900℃ for 2 hours; then the temperature was increased from 900℃ to 1200℃ at a heating rate of 3℃ / min and held at 1200℃ for 3 hours; finally, the temperature was cooled to 50℃ at a cooling rate of 5℃ / min.
[0041] Example 2 This embodiment provides a method for preparing porous ceramics using ultraviolet light-induced phase separation, which differs from Example 1 in that: The substances used are: 12.75g tripropylene glycol diacrylate (TPGDA), 4.25g polypropylene glycol (PPG), 80g alumina ceramic powder, 2g BYK-111, and 0.75g TPO.
[0042] The photopolymerization process parameters include: ultraviolet light wavelength 365nm, exposure dose 15mJ / cm². 2 .
[0043] The dried ceramic green body is degreased. The specific steps are as follows: the ceramic green body is transferred to a muffle furnace and heated from 50℃ to 600℃ at a heating rate of 0.5℃ / min in an air atmosphere. It is then held at 150℃, 250℃, 350℃, 500℃ and 600℃ for 6 hours respectively, so that the residual PEG, crosslinked PEGDA400, TPO and BYK-111 are gradually pyrolyzed and discharged to obtain alumina ceramic preform.
[0044] The remaining steps and parameters are the same as in Example 1.
[0045] Example 3 This embodiment provides a method for preparing porous ceramics using ultraviolet light-induced phase separation, which differs from Example 1 in that: The substances used are: 11.67g polyurethane acrylate (PUA1000), 5g polyvinylpyrrolidone (PVP), 85g barium titanate ceramic powder, 3g BYK-111, and 1g TPO.
[0046] The photopolymerization process parameters include: ultraviolet light wavelength 405nm, exposure dose 20mJ / cm². 2 .
[0047] The dried ceramic green body underwent degreasing treatment, specifically as follows: It was placed in a vacuum tube furnace, and under continuous nitrogen protection, the temperature was increased from 50℃ to 500℃ at a heating rate of 0.5℃ / min. The temperature was then held at 150℃, 250℃, 350℃, and 500℃ for 2 hours each, allowing residual PEG, cross-linked PEGDA400, TPO, and BYK-111 to gradually pyrolyze and dissipate, yielding an alumina ceramic preform. The alumina ceramic preform was then transferred to a muffle furnace, and the above heating and holding processes were repeated under an air atmosphere to oxidize and remove residual carbon formed during nitrogen pyrolysis.
[0048] The remaining steps and parameters are the same as in Example 1.
[0049] Example 4 This embodiment provides a method for preparing porous ceramics using ultraviolet light-induced phase separation. The difference from Example 1 is that the amounts of PEGDA400 and PEG200 added in this embodiment are 7.7g and 3.3g, respectively (the mass ratio of PEGDA400 to PEG200 is 7:3).
[0050] The remaining steps and parameters are the same as in Example 1.
[0051] Example 5 This embodiment provides a method for preparing porous ceramics using ultraviolet light-induced phase separation. The difference from Embodiment 1 is that the amounts of PEGDA400 and PEG200 added in this embodiment are 8.25g and 2.75g, respectively (the mass ratio of PEGDA400 to PEG200 is 7.5:2.5).
[0052] The remaining steps and parameters are the same as in Example 1.
[0053] Comparative Example 1 This comparative example provides a method for preparing ceramics. The difference between this comparative example and Example 1 is that PEG200 was not added. The remaining steps and parameters are the same as in Example 1.
[0054] Comparative Example 2 This comparative example provides a method for preparing ceramics. Compared with Example 1, the difference is that PEG200 is not added in this comparative example, but 2.2g of polyethylene oxide (PEO) is added as a non-photopolymerization phase separation component. The remaining steps and parameters are the same as in Example 1.
[0055] Comparative Example 3 This comparative example provides a method for preparing ceramics. Compared with Example 1, the difference is that PEG200 is not added in this comparative example, but 2.2g of PMMA is added as a pore-forming agent. The remaining steps and parameters are the same as in Example 1.
[0056] Comparative Example 4 This comparative example provides a method for preparing ceramics. The difference from Example 1 is that the masses of PEGDA400 and PEG200 used in this comparative example are 9.9 g and 1.1 g, respectively. The remaining steps and parameters are the same as in Example 1.
[0057] Comparative Example 5 This comparative example provides a method for preparing ceramics. The difference from Example 1 is that the masses of PEGDA400 and PEG200 used in this comparative example are 6.6 g and 4.4 g, respectively. The remaining steps and parameters are the same as in Example 1.
[0058] Performance testing The sintered ceramic samples were characterized in terms of size and pore structure, specifically including: 1. The surface microstructure of the sintered samples was observed using a scanning electron microscope, and the average pore size was statistically analyzed using ImageJ images; 2. The viscosity of the slurry was measured using a rotational rheometer; 3. The apparent porosity of the sample was measured based on the Archimedes displacement method.
[0059] like Figure 2As shown, in Comparative Example 1, no phase-separated components were introduced. The main characteristic was the presence of irregular residual pores between ceramic particles after particle accumulation. These pores were few in number and small in size (e.g., ...). Figure 2 As shown in a); in Comparative Example 3, after using a traditional PMMA pore-forming agent, larger isolated pores were observed, but the pore distribution was relatively discrete and the connectivity was limited (e.g., Figure 2 (as shown in b); In contrast, after photopolymerization-induced phase separation in Example 1, the ceramic framework remained continuous, the number of pores increased significantly, the pore size distribution was relatively uniform, and it showed a certain tendency to interconnect (e.g., as shown in b). Figure 2 (As shown in c). The above results indicate that photopolymerization-induced phase separation is beneficial for promoting micropore formation, improving pore openness and connectivity, and enhancing the uniformity of the internal pore structure of ceramics.
[0060] like Figure 3 As shown, the apparent porosities of Examples 1-3 were 19.2%, 20.5%, and 24.2%, respectively, and the average pore sizes were 5.9 μm, 6.7 μm, and 6.2 μm, respectively. The small variation indicates that the preparation method has good stability. Comparison of Examples 1 and 4-5 shows that when the PEGDA / PEG mass ratio decreased from 8:2 to 7:3, the apparent porosity increased from 19.2% to 23.8%, and the average pore size increased from 5.9 μm to 7.5 μm. This indicates that adjusting the mass ratio of PEGDA to PEG can effectively control the pore structure of ceramic materials.
[0061] In Comparative Example 4, with a PEGDA / PEG mass ratio of 9:1, the apparent porosity was only 12.5%, and the average pore size was 3.2 μm, resulting in fewer pore structures with weak connectivity. In Comparative Example 5, with a mass ratio of 6:4, the apparent porosity increased to 32.8%, and the average pore size increased to 12.6 μm. However, excessively high PEG content could lead to coarsening of the phase separation region and a reduction in the proportion of the ceramic skeleton. Furthermore, Comparative Example 1 showed that without PEG, the apparent porosity was only 3.2%, and the average pore size was 0.4 μm. Comparative Example 3, using the traditional PMMA pore-forming agent, had an apparent porosity of 7.4% and an average pore size of 1.9 μm, further demonstrating that photopolymerization-induced phase separation can effectively promote micropore formation and achieve controllable pore structure preparation.
[0062] like Figure 4 As shown, Examples 1-3 used PEG, PPG, and PVP as non-photopolymerization phase separation components, respectively. The resulting ceramic slurries all exhibited significant shear-thinning behavior, and at a shear rate of 100 s⁻¹, the slurries showed significant shear-thinning behavior. -1 The viscosities of all samples were below 3 mPa·s; in contrast, in Comparative Example 2, after using PEO, the ceramic slurry exhibited viscosity below 3 mPa·s at a shear rate of 100 mPa·s. -1The viscosity was approximately 7.5 mPa·s, indicating that the ceramic powder had good dispersion uniformity in the slurry. This suggests that PEG, PPG, and PVP can not only participate in photopolymerization-induced phase separation as non-photopolymerization components, but also improve the dispersion state of ceramic powder in the slurry and reduce the slurry viscosity, thus having the dual function of phase separation and pore adjustment and improving the rheological properties of the slurry.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing porous ceramics using ultraviolet light-induced phase separation, characterized in that, Includes the following steps: Step S1: Under light-protected conditions, ceramic powder, photocurable monomer, photoinitiator, non-photopolymerizable phase separation component and dispersant are mixed evenly to obtain ceramic slurry; Step S2: The above ceramic slurry is cured by light to obtain a ceramic green body; Step S3: Remove organic matter from the ceramic green body and perform sintering treatment to obtain a sintered ceramic body with a porous structure.
2. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 1, characterized in that, The photocurable monomer includes at least one of polyethylene glycol diacrylate, tripropylene glycol diacrylate, and polyurethane acrylate.
3. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 2, characterized in that, The non-photopolymerized phase-separated component includes at least one of polyethylene glycol, polypropylene glycol, and polyvinylpyrrolidone.
4. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 3, characterized in that, The mass ratio of the photocurable monomer to the non-photopolymerized phase-separated component is (7:3) to (8:2).
5. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 4, characterized in that, The pore size of the ceramic sintered body is 2.0~7.5μm.
6. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 1, characterized in that, In the ceramic slurry The mass fraction of ceramic powder is 75-85%; The mass fraction of the dispersant is 1-3%; The total mass percentage of the photocurable monomer and the non-photopolymerized phase-separated component is 11% to 23.5%. The photoinitiator accounts for 0.5% to 1% of the total mass.
7. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 1, characterized in that, In step S2, the photocuring process parameters include: ultraviolet light wavelength 355nm~405nm, and exposure energy 10~40mJ / cm. 2 .
8. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 1, characterized in that, Step S3, which involves removing organic matter from the ceramic green body, includes: The ceramic green body obtained in step S2 is cleaned and degreased to obtain a green body with a porous structure.
9. The method for preparing porous ceramics using ultraviolet light-induced phase separation as described in claim 8, characterized in that, The degreasing process includes: Place the ceramic green body in an air atmosphere and heat it to 500~600℃, then hold it at that temperature for 2~6 hours.
10. A porous ceramic, prepared by the method described in any one of claims 1-9.